History of Italian Philosophy. - Garin, Eugenio. (Value Inquiry Book Series, 2008)
This book is a treasure house of Italian philosophy. Narrating and explaining the history of Italian philosophers from the Middle Ages to the twentieth century, the author identifies the specificity, peculiarity, originality, and novelty of Italian philosophical thought in the men and women of the Renaissance. The vast intellectual output of the Renaissance can be traced back to a single philosophical stream beginning in Florence and fed by numerous converging human factors. This work offers historians and philosophers a vast survey and penetrating analysis of an intellectual tradition which has heretofore remained virtually unknown to the Anglophonic world of scholarship.